Analysis of characteristics of land use change and its ecological effects in the Datong River Basin - Li, Zhenlin; Qin, Xiang; Liu, Yushuo; Jin, Zizhen (Frontiers in Environmental Science, 2025)
Based on the lack of understanding of the attribution of land use change and the resulting ecological effects in the Datong River Basin (DTRB), we analyzed the spatial-temporal characteristics of the land use change and explored the drivers of the changes, and calculated the effect of the land use change on the net primary productivity (NPP) from 1990 to 2020. The main conclusions are as follows: The predominant land use types comprised grassland, forest, cropland, bare land, ice/snow and other categories. The cropland, grassland and shrubs showed a decreased trend. However, forest, bare land and impervious surface were increased. The comprehensive index of the land use degree showed a significant downward trend, indicating that land use intensity will likely remain at a low level. Additionally, these conversions occurred among different land use types. Cropland and Grassland were dominated by transfer-out; Forest, bare land and impervious surface were dominated by transfer-in. Regarding the analysis of the driving factors of land use changes. The low elevation area was affected by human activities, and under the impact of “green gain” protection policy, the area of grassland increased; coupled with the impact of “returning farmland to forests,” the area of cropland decreased. Bare land was significantly and negatively correlated with GDP and population, while impervious surface was positively correlated. However, high-altitude areas were affected by natural factors, with grassland partial negatively correlated with precipitation. For bare land, it partial positively correlated with temperature. Snow/ice partial positively correlated with precipitation. Regarding the ecological effect of land use change, the multi-year average NPP was about 167.0 gC·m−2·a−1 and showed a decreased trend during the period of 1990–2020, and the NPP decreased in the northwest and increased in the southeast. This study provides scientific suggestions for the management of land resources and ecological environmental protection.